Importance of Learning Styles Magnitude In Education: Understanding the Impact of Learning Styles on Effective Teaching (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In present situation the whole education actuallyoperates in classroom which focuses upon communicating the necessary knowledgeand skills effectively to its recipient. However, the teaching is very delicateand complex activity carried out in the classroom. Galloway (1976) says,"The teacher must also be effective teaching, especially for those childrenwhom he identifies as poor learners, since the simple truth is that poorlearning usually follows that effective instruction is a major contributor tolearning and that for child who is not learning and that for child who is notlearning well, instruction is ineffective. Thus, the questions emerge as to howa teacher could become effective for each of his students. (Agarwal 1983)Classroom observation reveal the basic fact that students differ in theirreaction time, in the amount of encouragement, they need to attack learningtask, in term of amount, frequency and type of motivation they require, in waysin which they deal with a given task and so on. Teaching is made adaptive tothe differences which exist among the learners with regard to their style of perceiving,capacity the independent works, willingness, level and pace of attention. Forplanning a system instruction, different type of motivation about the learnersare needed, besides the information about students, from which social class dothey come, what are interests and abilities etc. it is very important to knowas to what are the style of the students for learning in general and forlearning a particular content? Do they very significantly? What types oflearning procedures and activities promote the most repaid and successfullearning in the students, who have deeply ingrained patients for their ownlearning?